Avaliação da qualidade físico-química e sensorial de patês de ovino e de caprino com castanha portuguesa - Almeida, Samanta Kelli (2019)
The overall objective of this work was to test the physical-chemical and sensorial quality of a meat paste (pâté), formulated with sheep meat and goat's and Portuguese cashew nuts. The animals used to carry out this work were Churra Galega Bragançana sheep and Serrana goats. They had a carcass weight of approximately 20 kg and aged between 5 and 9 years. The chestnut used was the species Castanea sativa Mill. The Pates were prepared in the Laboratory of Technology and Quality of Meat and Carcass of the Higher Agricultural School of the Polytechnic Institute of Bragança. For each species, three types of pâtés were manufactured, with the difference in the processing of the chestnut, so that the treatments were: goat or sheep with raw or cooked or dehydrated chestnut. In goat meat pâtés the pH values were higher, which contributed to higher values in the oxidation indexes for this species. The process of dehydration of the chestnut resulted in pates with lower humidity than the others. The antioxidant properties of the compounds present in the nuts contributed to the reduction of oxidation rates, acting as a natural preservative. As for the product characterization through the attributes evaluated by the consumers, the pates with cooked chestnuts were considered of homogeneous appearance and sweet taste. The raw chestnut reduced the cohesiveness of pates in both species, while dehydration resulted in products of sweet taste, but with grainy texture. The goat's meat pâté with cooked chestnuts was preferred by consumers being characterized as a homogeneous product with good cohesiveness.